Diseño modular multifuncional en espacios reducidos - Cordero Pasquel, Mónica Jajaira (2023)
Through the research process, this project was based on the current situation of small work spaces, specifically in spaces for the sale of flowers that are located on doce de noviembre avenue in the city of Ambato, which have a lack of interior design, either to reduce costs or lack of knowledge of design, thus these spaces are part of a social problem that results in work spaces that have no functionality, improvised spaces without considering the needs and requirements of the users. The objective of this project is to establish a multifunctional system for small workspaces that can be habitable, so it is proposed as a solution the application of modularity and multifunctionality that will be applied in furniture in order to generate comfortable spaces that allow the user to connect with the space and perform their activities without difficulty, as a methodology was taken into account the user-centered design as a tool to obtain a functional product for the individual considering different factors such as materiality, needs, requirements and other aspects that contribute to the final project.